Driving Policy Support A Mixed-Methods Analysis of Public Perception, Health Risks, and Vehicle Emissions in Urban Indonesia - Ilham Ilham; Reynard Ade Asfihan Yuana (Westscience Press, 2026)
This study evaluates public perception regarding the impact of vehicle emissions on urban air quality in Indonesia, focusing on the interplay between traffic density, vehicle types, and public awareness levels. It aims to bridge the research gap concerning how specific knowledge of pollution sources and health risk perceptions mediate support for emission control policies in major metropolitan areas. A mixed-methods approach was employed, integrating quantitative surveys (n=500) and in-depth qualitative interviews (n=50) across high-density urban regions. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) for hypothesis testing and NVivo thematic analysis to explore the subjective experiences of respondents. Findings reveal a highly significant positive correlation (β = 0.68) between traffic density and negative air quality perception, where chronic congestion fosters a heightened